Socio-Scientific Issues Based Introduction (SSIBI) in Elementary School IPAS Learning: A Theoretical and Empirical Review - Rahmanto, Septian Eko; Suryandari, Kartika Chrysti; Rawanoko, Endrise Septina (Universitas Sebelas Maret, 2026)
IPAS learning in elementary schools is still largely teacher-centered and insufficiently connected to real-life contexts, resulting in low conceptual understanding and limited student engagement. This study aims to examine theoretically and empirically the implementation of the Socio Scientific Issues Based Introduction (SSIBI) model in elementary school IPAS learning. The method employed is a literature review by analyzing various sources, including national and international journal articles, textbooks, and relevant previous studies related to the SSIBI model, socio-scientific issues–based learning, and conceptual understanding in IPAS. The analysis was conducted using a descriptive qualitative approach to identify theoretical foundations, model characteristics, and empirical findings regarding the effectiveness of SSIBI. The results of the review indicate that the SSIBI model is grounded in social constructivist theory and meaningful learning, encouraging students to construct conceptual understanding through discussion, analysis of real-world issues, and science-based decision making. Empirical evidence shows that the implementation of SSIBI is effective in improving students’ conceptual understanding of IPAS, scientific literacy, critical thinking skills, and active participation in learning. In addition, the model produces nurturant effects in the form of strengthened scientific attitudes, social awareness, and student character development. Therefore, it can be concluded that the Socio Scientific Issues Based Introduction (SSIBI) model is an effective and relevant instructional approach for improving the quality of IPAS learning in elementary schools.